STUDENT’S LANGUAGE LEARNING STRATEGIES IN SPEAKING - Sudharni Sudharni; Urai Salam; Endang Susilawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractThis study was aimed to describe language learning strategies used by a third semester student of English Education Study Program whose competence at English speaking. This research was a qualitative research. The subject of this study was a successful language learner in the third semester. This research was a case study which used interview and document as the instruments of data collecting. In the interview, the researcher asked the participant to answer questions that focused on the metacognitive strategies used by him. The document was provided in order to support the primary data. Based on the result, the third semester student whose competence at English speaking skill used the four representative strategies which proposed by O’Malley and Chamot (1990) in his learning process. The first representative strategy used by the student was selective attention. The second was planning. The third was asking for people’s perspective towards self performance, reviewing how the task was going and detecting any error happened on the track. The fourth was evaluation which included keep applying the same activity as the strategy after knowing that the strategy worked and changing the way he performed depending on the other speaker.Keywords: Language Learning Strategies, Speaking